Efetividade do tratamento da rinite alérgica nos pacientes atendidos no serviço de otorrinolaringologia do Hospital Universitário Bettina Ferro de Souza - LIMA, Daniel Cruz Limeira (2023)
Allergic Rhinitis (AR) is a disease of high frequency in practice daily clinic, being a chronic disease that affects the quality of the individual's life not only for the breathing alteration, but also for the damages behavioral, functional and physical that causes. Under the initiative ARIA (Allergic Rhinitis and Its Impact on Asthma) and World Health Organization (WHO) classifies AR in: intermittent or persistent; mild, moderate or severe. This work aims to: assess the effectiveness of drugs proposed (antihistamines, oral steroids, topical nasal corticosteroids) by the protocol of Otorhinolaryngology of University Hospital Bettina Ferro de Souza (HUBFS) applied to patients enrolled in the Division of Rhinology from September 2010 to February 2011, noting the clinical course of patients, complications and side effects after therapeutic institution, and describe some aspects of sociodemographic study population. This research has the character of clinicalepidemiological cross. The study sample had an absolute number of records of 50 patients with AR who fit the following inclusion criteria: patients aged between two and sixty years presenting with symptoms characteristic of AR. Were excluded from the study those who were against the criteria listed above. The results showed that all patients classified as having mild intermittent AR showed improvement, followed by those with AR Intermittent moderate / severe or mild persistent AR (75%). The group had a lower percentage of remission of symptoms (61.29%) was diagnosed with AR of moderate / severe persistent.